Applying media synchronicity theory to distance learning in virtual worlds: a design science approach. (1st January 2014) - North-Samardzic, Andrea; Braccini, Alessio Maria; Spagnoletti, Paolo; Za, Stefano
The use of 3D virtual world platforms in learning is growing in popularity. While there are many learning affordances for such environments, including the possibility of doing things impossible in reality, there are some noted drawbacks. In particular the way they can be used for distance learning deserves consideration. In this paper, we focus on the issue of synchronicity and on how it limits the flexibility that distance learning affords. We use e-learning theory and media synchronicity theory to propose an explanatory design theory for distance learning using 3D virtual world to address the problem of synchronicity.